COVID-19 PANDEMIC AND CHALLENGES IT POSES TO OTORHINOLARYNGOLOGISTS - V. Stoyanov (Trakia Journal of Sciences)
As doctors, we all have a shared responsibility in terms of COVID-19. At first glance, ENT specialists are not classed as the so-called “front line” medical workers but have a key role to play and these needs to be addressed. In response to the pressures on the Health Care System, the medical care provided by otorhinolaryngologists has been limited. Irrespective of the imposed work limitations, patients will still need to be provided with the specific care, which requires us to find the best solutions for work stations and wards. In addition, measures should be put in place to avoid compromising surgical activity (especially emergency procedures), deriving from a combination of factors, including staff sickness, problems with the supply of medical equipment, the use of operating theaters, anesthesiological teams, etc. An increased number of performed tracheostomies are expected in positive COVID-19 patients who need artificial pulmonary ventilation. The purpose of this paper is to address all these issues, based on current and accessible information, and propose measures and procedures for otorhinolaryngologists in the context of the COVID-19 pandemic for different patient groups. Simultaneously, recommendations are made to protect the doctors and their teams, as well as to reconfigure the medical operations in the new conditions.